Jaringan Sosial Irwan Mangga Pada Pemilihan Legislatif Tahun 2019 di Sorong Kepulauan - Tanel, Ester Yulina; Ali, Muhammad; Banggu, Masni; Purwanti, Nanik; Abdul Kadir, Muhammad Arifin (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
This research aims to describe and analyze the use of social network and campaign strategy for Irwan Mangga as a legislative candidate in the 2019 legislative general election in Sorong Islands. A qualitative approach is used as a research method in this paper with a descriptive type of analysis. Data collection through interviews with people who are considered related to the author's research, and literature reviews in the form of articles that have the same research theme. The research results show that Irwan Mangga's social capital is utilized through three social network relationships. First, work networks through his work as an owner and technician in his own workshop. Second, relationships with local groups through support from fishing groups in the Sorong Islands. And third, the Taklim Council network, Irwan Mangga as a lecturer at several mosques and taklim assembly study groups